Main challenges, trends and opportunities for wine tourism in Portugal - Santos, Vasco (2018)
Purpose – This paper aims to define the boundaries of wine tourism to identify the main challenges, trends and opportunities of wine tourism in Portugal, providing some critical recommendations for those operating in this sector. Design/methodology/approach – The paper draws on a literature review and content analysis of prior and ongoing work. Findings – The main challenges, trends and opportunities for the wine tourism industry in Portugal are identified, as well as suggestions and practical recommendations/contributions for managers, stakeholders, players and marketers. The paper concludes with some key points that could form the basis of a strategic agenda for future action. Originality/value – Based on the reviewed literature, some benchmarks for the wine tourism industry in Portugal were developed.